IMPORTANCE OF PAINTING AND SCULPTURE IN ARCHITECTURAL EDUCATION AND TEACHING METHODOLOGY - Kuchkarov Bakhodir Olmasovich (American Journals, 2024)
Architectural education occupies an important place in modern society. This area is not only concerned with the design and construction of buildings, but also includes aesthetic and functional aspects. The subjects of painting, painting and sculpture are central to architectural education and play an important role in the development of architects ' creative abilities.